Foreløbig Beretning til Indenrigsministeriet om Tilvirkning af fersk Smør. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Foreløbig Beretning til Indenrigsministeriet om Tilvirkning af fersk Smør.